Gray Market Controversies: The 1980s and Beyond - Lipner, Seth E. (Tufts Archival Research Center, 2005)
Volume 13, Issue 2. Summer Gray market goods are genuine trademarked goods, imported without the permission of the local trademark owner. These goods are manufactured by a trademark owner or authorized representative abroad and usually are similar in quality to their authorized counterparts. While much has been written about the world gray market, most articles deal in generalities, anecdotes, and doctrine, as opposed to facts about actual gray market channels. Seth E. Lipner explores what recent court cases, including a US Supreme Court decision, have revealed about the gray market business, and he discusses the international ramifications and legal issues behind those decisions.